Repurposing Antispasmodic Agent Otilonium Bromide for Treatment of Staphylococcus aureus Infections - Zhou, Linying; She, Pengfei; Tan, Fang; Li, Shijia; Zeng, Xianghai; Chen, Lihua; Luo, Zhen; Wu, Yong (Frontiers in Microbiology, 2020)
Recently, the problem of bacterial resistance has been brought into focus, which makes the development of new antibiotics become a necessity. Compared with traditional development approaches, drug repurposing provides a faster and more effective approach to find new antimicrobial agents. In this study, we found that antispasmodic agent otilonium bromide had strong antibacterial ability and bactericidal activity against Staphylococcus aureus, with minimal inhibitory concentrations (MICs) of 4–8 μg/ml, and bacteria could be killed completely after treatment with 2× MIC of otilonium bromide for 5 h. Furthermore, it had a potent effect on eradicating biofilm at concentrations ranging from 16 to 64 μg/ml. At the same time, it had low tendency to develop resistance and possessed limited cytotoxicity. In the methicillin-resistant S. aureus–infected mouse peritonitis model, it was also effective to cure mice and improve their survival rate. In addition, we observed that otilonium bromide changed the permeability of bacterial membrane and caused membrane damage, and it is probably the antibacterial mechanism of otilonium bromide. Taken together, our results indicated that otilonium bromide could be a new antimicrobial agent to treat S. aureus infections more safely and efficiently.